USE OF ANTICOAGULANT IN COVID-19 PATIENTS AT PKU MUHAMMADIYAH GAMPING HOSPITAL YOGYAKARTA - Nurhasani -; Woro Supadmi; Endang Yuniarti (Universitas Muhammadiyah Magelang, 2023)
Based on WHO data, there is about 14% average of patients who suffer from a severe level of Covid-19 disease and 5% of patients admitted to the ICU (Intensive Care Unit) are known to have symptoms of thromboembolism and coagulopathy disorders. The current management of Covid-19 therapy requires heparin. This research aims to find out the accuracy of the heparin regimen, to determine the improvement of the patient's clinical condition, the side effects of heparin based on clinical response, to analyze the relationship between the accuracy of the therapeutic regimen and the improvement of the patient's clinical condition, and also to know the incidence of side effects after heparin use. The type of this research was descriptive-analytic with a cohort design with retrospective data collection. The data were collected by taking medical records at PKU Muhammadiyah Gamping Hospital Yogyakarta. Moreover, the data were collected including heparin therapy regimens with subjective condition and patient objective during the therapy. The data obtained were analyzed by using univariate analysis technique and bivariate analysis technique. The results showed there were 61 patients who fulfilled the inclusion criteria. The evaluation of the accuracy the heparin therapy regimen obtained 95.08% correct results and 4.92% incorrect results. The analysis result of the accuracy the therapeutic regimen showed a significant relationship with clinical improvement with parameters APTT number (p=0.006; RR=0.155; CI = 0.085-0.283). Whereas, there was not found a significant relationship between the accuracy of the therapeutic regimen with the incidence of side effects (p>0.05).